Crystal structure of the TreS:Pep2 complex, initiating α-glucan synthesis in the GlgE pathway of mycobacteria - Kermani, Ali A. (J Biol Chem, 2019)
A growing body of evidence implicates the mycobacterial capsule, the outermost layer of the mycobacterial cell envelope, in modulation of the host immune response and virulence of mycobacteria. Mycobacteria synthesize the dominant capsule component, α(1→4)-linked glucan, via three interconnected and potentially redundant metabolic pathways. Here, we report the crystal structure of the Mycobacterium smegmatis TreS:Pep2 complex, containing trehalose synthase (TreS) and maltokinase (Pep2), which converts trehalose to maltose 1-phosphate as part of the TreS:Pep2–GlgE pathway. The structure, at 3.6 Å resolution, revealed that a diamond-shaped TreS tetramer forms the core of the complex and that pairs of Pep2 monomers bind to opposite apices of the tetramer in a 4 + 4 configuration. However, for the M. smegmatis orthologues, results from isothermal titration calorimetry and analytical ultracentrifugation experiments indicated that the prevalent stoichiometry in solution is 4 TreS + 2 Pep2 protomers. The observed discrepancy between the crystallized complex and the behavior in the solution state may be explained by the relatively weak affinity of Pep2 for TreS (K(d) 3.5 μm at mildly acidic pH) and crystal packing favoring the 4 + 4 complex. Proximity of the ATP-binding site in Pep2 to the complex interface provides a rational basis for rate enhancement of Pep2 upon binding to TreS, but the complex structure appears to rule out substrate channeling between the active sites of TreS and Pep2. Our findings provide a structural model for the trehalose synthase:maltokinase complex in M. smegmatis that offers critical insights into capsule assembly.